Trichinella spiralis Thioredoxin Peroxidase 2 Regulates Protective Th2 Immune Response in Mice by Directly Inducing Alternatively Activated Macrophages - Jin, Qi-Wang; Zhang, Nian-Zhang; Li, Wen-Hui; Qin, Hong-Tao; Liu, Yin-Ju; Ohiolei, John Asekhaen; Niu, Dong-Yu; Yan, Hong-Bin; Li, Li; Jia, Wan-Zhong; Song, Ming-Xin; Fu, Bao-Quan (Frontiers in Immunology, 2020)
Trichinella infection has been identified to induce macrophages into alternatively activated phenotype, which are primarily associated with the development of a polarized Th2 immune response. In the present study, we examined the immunomodulatory effect of T. spiralis thioredoxin peroxidase-2 (TsTPX2), a protein derived from T. spiralis ES products, in regulation of Th2 response through directly activing macrophages, and evaluated the potential of TsTPX2 as a vaccine candidate against T. spiralis infection. The location of TsTPX2 was detected by immunohistochemistry and immunofluorescence analyses. The Th2 response in vivo induced by rTsTPX2 was characterized by testing cytokines (IL-4 and IFN-γ) and T cells in the peripheral blood. The rTsTPX2-activated macrophages were tested polarization, the ability of evoking native CD4+ T cells and resistance to the larval infection after adoptive transfer in BALB/c mice. The immunolocalization analysis showed TsTPX2 in cuticles and stichosome of T. spiralis ML. The immunostaining was detected in cuticles and stichosome of T. spiralis Ad3 and ML, as well as in tissue-dwellings around ML, after the intestines and muscle tissues of infected mice were incubated with anti-rTsTPX2. Immunization of BALB/c mice with rTsTPX2 induced a Th2-bias response in view of the high levels of IL-4 production and CD4+ T cell proliferation along with the low levels of IFN-γ and CD8+ T cells. In vitro studies showed the rTsTPX2 could directly drive RAW 264.7 and peritoneal macrophages to the alternatively activated phenotype characterized by the up-regulated expression of genetic markers, including Arg-1 and Mrc-1. The rTsTPX2-activated peritoneal macrophages could promote CD4+ T cells polarized into Th2 type characterized by the increased IL-4 and decreased IFN-γ secretion. Adoptive transfer of rTsTPX2-activated peritoneal macrophages into mice induced a typical Th2 response and exhibited a 44.7% reduction in adult worms upon challenged with T. spiralis infective larval. Our study suggested that TsTPX2 would be a potential vaccine candidate against trichinosis in mouse model as one of secretions in regulation of Th2 immune responses through directly alternatively activated macrophages during T. spiralis infection, and should warrant further studies in other helminths.